Development of key-dependent dynamic S-Boxes with dynamic irreducible polynomial and affine constant - Agarwal, Praveen; Singh, Amandeep; Kilicman, Adem (SAGE Publications, 2018)
In recent years, the need to develop advanced information technology systems in the area of mechanical engineering has been growing continuously to deliver better product quality at reduced cost. Embedding the electronics and software with machines transform them into smart machines sophistically called mechatronic. These software-oriented machines collect big data using sensors and other electronics and share among other smart machines, which further helps them in controlling the manufacturing processes, decision-making, and even in maintenance. Machine-to-machine sharing of data involves the risk of data stealing or modification, which may further disrupt the working of manufacturing process and leads to poor quality product. For data security, block ciphers like advanced encryption standard are needed. Advanced encryption standard is an encryption algorithm which is widely used to provide security to sensitive information by organizations. The main core of advanced encryption standard is its non-liner component that is S-Box, which is also called substitution table. The S-Box provides confusion capabilities in algorithm. The point of interest for cryptanalysis and hackers is S-Box, which is fixed in case of advanced encryption standard. Cryptanalysis and hackers exploit this weakness of advanced encryption standard. Many researchers tried to modify S-Box using different techniques. In this article, we tried to create dynamic S-Boxes which are key-dependent and, at the same time, they are using dynamic irreducible polynomial and affine constant.